Potential applications of microstrip devices with traveling wave resonators - Glushechenko, E. N. (Technology and design in electronic equipment, 2013)
The shortcomings of the known microwave filters in microstrip lines are considered, the advantages of the use of directional traveling-wave filters in microstrip performance and examples of their potential applications are shown.